1997
DOI: 10.1038/sj.bjp.0701272
|View full text |Cite
|
Sign up to set email alerts
|

Capsazepine block of voltage‐activated calcium channels in adult rat dorsal root ganglion neurones in culture

Abstract: 1 We have found that capsazepine, a competitive antagonist at the vanilloid (capsaicin) receptor, blocks voltage-activated calcium currents in sensory neurones. 2 The block of calcium current was slow to develop with a half time of about one minute at 100 mM and lasted for the duration of the experiment. The rate of block of calcium current was strongly concentration-dependent. 3 The EC 50 for the blocking e ect at 0 mV was 7.7+1.4 mM after 6 min exposure to capsazepine. The EC 50 at equilibrium was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
144
4
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(155 citation statements)
references
References 23 publications
4
144
4
3
Order By: Relevance
“…Our results correlate with other studies that have seen effective concentrations of capsaicin in the micromolar range (17,18), whereas vanilloid receptor can be activated with concentrations in the nanomolar range. Our results also agree with reports of some capsaicin-mediated effects not correlating with typical features of the unusual responses of vanilloid receptors to vanilloid antagonists (49).…”
Section: Discussionsupporting
confidence: 83%
“…Our results correlate with other studies that have seen effective concentrations of capsaicin in the micromolar range (17,18), whereas vanilloid receptor can be activated with concentrations in the nanomolar range. Our results also agree with reports of some capsaicin-mediated effects not correlating with typical features of the unusual responses of vanilloid receptors to vanilloid antagonists (49).…”
Section: Discussionsupporting
confidence: 83%
“…Pretreatment with the TRPV1 receptor antagonist capsazepine prior to cannabidiol and MK-801 elicited a disruption of PPI similar to that observed with vehicle and MK-801 alone, suggesting that TRPV1 receptors may be involved in the restorative effect of cannabidiol on MK-801-induced disruption of PPI. However, although capsazepine has been shown to reverse capsaicin-induced effects such as dopaminergic cell death induced in vivo by intranigral injection (Kim et al, 2005) and to reverse antihyperalgesic effects of cannabidiol in rats (Costa et al, 2004), it has also been shown to block calcium channels and nicotinic cholinergic receptors at the same doses at which it blocks the TRPV1 receptor (Docherty et al, 1997;Liu and Simon, 1997), making it difficult to conclusively identify the involvement of TRPV1 receptors in the effect of cannabidiol in the present study. In preliminary experiments in our laboratory with systemic administration of the potent and selective TRPV1 antagonist iodoresiniferatoxin, hypomotility and accompanying hypothermia (unpublished observations) resulted in the startle response being too low for use in obtaining meaningful PPI data.…”
Section: Discussionmentioning
confidence: 70%
“…Capsazepine at a concentration ≥ 1 μM acts in a non-specifi c manner in rat dorsal root ganglion neurons by blocking voltage-activated calcium currents. However, IC 50 for a blocking response induced by capsaicin is lower: 0.1-0.7 μM (Docherty et al, 1997). We recorded inhibiting effect of capsazepine on 0.1 μM capsaicin.…”
Section: Discussionmentioning
confidence: 99%